Intracellular association of the protein product of the c-myc oncogene with the TATA-binding protein. - Maheswaran, S (1994)
The c-myc proto-oncogene encodes nuclear phosphoproteins that bind DNA in a sequence-specific fashion and appear to function as transcriptional activators. Here we demonstrate that a 40-kDa nuclear protein coimmunoprecipitated with c-Myc specifically when nuclear proteins, extracted from nuclei of exponentially growing murine B-lymphoma WEHI 231 cells by using procedures for preparation of trans-acting factors, were reacted with anti-c-Myc antibodies made against different regions of the c-Myc protein. In contrast, preparation of nuclear lysates under denaturing conditions significantly reduced this coprecipitation. Upon incubation of WEHI 231 cells with the reversible chemical cross-linking agent dithiobis(succinimidyl propionate), the 40-kDa protein could be cross-linked to c-Myc protein intracellularly. Identification of the 40-kDa protein as the TATA-binding protein (TBP) of the TFIID transcription initiation complex was made by comigration and V-8 protease mapping, which yielded identical peptide fragments upon digestion of the 40-kDa protein and material immunoprecipitated with an anti-TBP specific antibody. Furthermore, in vitro-translated TBP bound to the amino-terminal portion of c-Myc. Column chromatography of cross-linked nuclear proteins showed TBP to be in a large-molecular-weight complex with c-Myc, consistent with a transcription initiation complex. These results indicate that intracellularly, c-Myc interacts with TBP, suggesting a mechanism of interaction of this oncoprotein with the basal transcription machinery.